2021
DOI: 10.1515/jpem-2020-0671
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetes in children and adolescents in Dhaka, Bangladesh

Abstract: Objectives Bangladesh has limited information regarding incidence of type 1 diabetes (T1D) and type 2 diabetes (T2D) in young people. The objective of this study was to measure minimum incidence of T1D and T2D, and record other types of new-onset diabetes in children and adolescents <20 years (y), in Dhaka District, Bangladesh, from 2011–2018. Methods Retrospective study using clinical records from Diabetic Association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Moreover, T1D incidence in younger than 15 years age group was 1.04 in 2011 and 1.42 in 2018. In this study, there was no significant increase in the incidence of childhood T1D over 2011–2018 [15].…”
Section: Reviewcontrasting
confidence: 60%
“…Moreover, T1D incidence in younger than 15 years age group was 1.04 in 2011 and 1.42 in 2018. In this study, there was no significant increase in the incidence of childhood T1D over 2011–2018 [15].…”
Section: Reviewcontrasting
confidence: 60%
“…The potential for misclassification can also occur in childhood and adolescent populations as well, due to the heterogeneity of T1D [ 18 , 19 ], which appears to be more pronounced in sub-Saharan Africa and South Asia [ 5 , 20 ].…”
Section: Data Limitationsmentioning
confidence: 99%
“…In addition, the increase in childhood-onset diabetes in Bangladesh is concerning. A retrospective study conducted using the clinical records of the diabetic association of Bangladesh revealed that from 2011 to 2018, in total, 725 children and adolescents (< 20 years old) were diagnosed diabetic, with a 12% average annual increase in the incidence of type 2 diabetes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%